2021
DOI: 10.1063/5.0046243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness on metal-to-semiconductor transition in 2-dimensional TiN thin films

Abstract: Titanium nitride thin films have been grown on c-plane sapphire substrates using a pulsed laser deposition technique in the thickness range of 6–45 nm. X-ray diffraction (XRD) analysis has demonstrated TiN (111) as the preferred orientation of growth on the sapphire substrates. The XRD measurements have also indicated that orientational alignment between the TiN and the sapphire improved with an increase in the TiN film thickness. A change in the resistivity behavior of the TiN thin films from metallic to semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…This behavior is attributed to the size effect of islands in an almost non-continuous thin-film structure. Applying the idea of the density of states and the Fermi function in region I, it can be shown that E normalg N E D 3 and normalΔ E 1 D 3 . , As shown schematically in Figure b, the separation between energy states (Δ E ) and the separation between the valence and conduction band (i.e., bandgap, E g ) increase with a reduction in the island dimension ( D ). If Δ E is more than E g , the excitation of an electron from the valence band to the conduction band is restricted and unoxidized TiN films, which should have ideally behaved metallic, start exhibiting high resistivity and semiconductor characteristics…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is attributed to the size effect of islands in an almost non-continuous thin-film structure. Applying the idea of the density of states and the Fermi function in region I, it can be shown that E normalg N E D 3 and normalΔ E 1 D 3 . , As shown schematically in Figure b, the separation between energy states (Δ E ) and the separation between the valence and conduction band (i.e., bandgap, E g ) increase with a reduction in the island dimension ( D ). If Δ E is more than E g , the excitation of an electron from the valence band to the conduction band is restricted and unoxidized TiN films, which should have ideally behaved metallic, start exhibiting high resistivity and semiconductor characteristics…”
Section: Resultsmentioning
confidence: 99%